Factors Associated to Growth Disorder in Children with Thalassemia Major - Nurbaiti Annisaa Soegiharto; Meiyanti Meiyanti (Global Medical & Health Communication (GMHC), 2021)
Growth disorders in short stature are often found in patients with β-thalassemia major. It is caused by several factors such as hypoxia, hemosiderosis, deficiency of nutritional intake, and micronutrient. Disorder in growth will affect the patient's quality of life. This study aims to determine the prevalence of growth disorders and analyze the factors associated with thalassemia child growth disorders. This study used an observational analytic study with a cross-sectional design on 167 patients with β-thalassemia major at the Palang Merah Indonesia Hospital, Bogor, West Java, in October–December 2018. Data was collected using a transfusion compliance questionnaire and the Morisky Medication Adherence Scale (MMAS-8), while growth was assessed using the CDC 2000 height/age curve. Data analysis used SPSS for Windows version 21.0. Of 167 subjects, 86 subjects (51.5%) were not adherent to transfusion, 97 subjects (58.1%) had low consumption of chelation iron, and 146 subjects (87.4%) had growth problems. The results of bivariate data analysis using the chi-square test for transfusion compliance and parental education on growth obtained p=0.000 and p=0.032. Likewise, for compliance with iron chelation consumption and parents' income to growth, the p value=0.000 was obtained. It was concluded that the prevalence of growth disorders was 87.4%, and there was a relationship between transfusion compliance, parental education level, parents' income, and compliance with iron chelation consumption on growth disorders in thalassemia children. FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN PERTUMBUHAN PADA ANAK TALASEMIA MAYORGangguan pertumbuhan berupa perawakan pendek sering ditemukan pada penderita talasemia β mayor. Hal ini disebabkan oleh beberapa faktor seperti hipoksia, hemosiderosis, kekurangan asupan nutrisi, dan mikonutrien. Gangguan pertumbuhan akan memengaruhi kualitas hidup pasien. Penelitian ini bertujuan mengetahui prevalensi gangguan tumbuh kembang dan menganalisis faktor-faktor yang berhubungan dengan gangguan tumbuh kembang anak talasemia. Penelitian ini menggunakan jenis penelitian observasional analitik dengan desain cross-sectional pada 167 pasien talasemia β mayor di RS Palang Merah Indonesia, Bogor, Jawa Barat pada bulan Oktober–Desember 2018. Pengumpulan data dilakukan dengan menggunakan kuesioner kepatuhan transfusi dan Morisky Medication Adherence Scale (MMAS-8), sedangkan pertumbuhan dinilai menggunakan kurva tinggi/usia CDC 2000. Analisis data menggunakan SPSS for Windows versi 21.0. Dari 167 subjek, 86 subjek (51,5%) tidak patuh pada transfusi, 97 subjek (58,1%) memiliki konsumsi kelasi besi rendah, dan 146 subjek (87,4%) mengalami gangguan pertumbuhan. Hasil analisis data bivariat menggunakan uji chi-square untuk kepatuhan transfusi dan pendidikan orangtua tentang pertumbuhan diperoleh p=0,000 dan p=0,032. Begitu pula untuk kepatuhan konsumsi kelasi besi dan pendapatan orangtua terhadap pertumbuhan diperoleh p=0,000. Disimpulkan bahwa prevalensi gangguan tumbuh kembang sebesar 87,4% dan terdapat hubungan kepatuhan transfusi, tingkat pendidikan orangtua, pendapatan orangtua, dan kepatuhan konsumsi kelasi besi dengan gangguan tumbuh kembang anak talasemia.